Liberalisme Dalam Pendidikan Islam Di Perguruan Tinggi - Imanuddin Abil Fida (JIE (Journal of Islamic Education), 2016)
This article departs from the fact that the law in Indonesia is buried. Although the education is not the main factor which is caused to the bad of law, but the Islam education is play a siginifacant role for the law. It is because Islamic education is ‘the main school’ for law enforcer. In term of law, the knowledge of morality, justice, liberty and truth must be the most important subject in order to product law enforcer with their morality. In fact, those values is abused. Therefore, Islamic education as one of the main subject in universities have to play an important role with the good construction of knowledge. It is because Islamic education will shape the worldview of students in their live. When their worldview is problematic, we can not expect litigious society. This article reveals that the concept of Islamic education which is based on al-Qur’an and the Sunnah has close link with law. It is unfortunate if the concept of Islamic education which is taught in universities was wrong so as produce people who do not care laws.